The Effect of Guided Inquiry Model Assisted by Interactive PowerPoint Media on High School Students' Learning Outcomes in Chemical Bonding Material - Avella Anastasya Gonti Sidebang; Herlinawati (Universitas Lampung, 2026)
The Effect of Guided Inquiry Model Assisted by Interactive PowerPoint Media on High School Students' Learning Outcomes in Chemical Bonding Material. This study aims to determine the effect of guided inquiry learning model assisted by interactive PowerPoint media on learning outcomes and to determine differences in students' conceptual understanding of chemical bonding material. This study used a quasi-experimental method with a non-equivalent control group pretest-posttest design. The population in this study were all grade X students of SMA Negeri 1 Lubuk Pakam in the 2025/2026 academic year. The research sample consisted of two classes selected by random sampling, namely the experimental class using guided inquiry learning model assisted by interactive PowerPoint and the control class using conventional learning assisted by regular PowerPoint, each totaling 36 students. Data collection techniques were carried out through learning outcome tests in the form of pretests and posttests. Data analysis techniques used included normality tests, homogeneity tests, N-Gain tests, and hypothesis tests using two-tailed t-tests. The results showed that the average value of student learning outcomes in the experimental class was higher than the control class. The N-Gain value in the experimental class was 0.916 with a very high category, while in the control class it was 0.777 with a very high category. The results of the hypothesis test indicate that there is a significant influence of the use of a guided inquiry learning model assisted by interactive PowerPoint media on student learning outcomes. Based on the results of the study, it can be concluded that the guided inquiry learning model assisted by interactive PowerPoint media is effective in improving student learning outcomes and conceptual understanding of chemical bonding material.